Evaluation of the effect of experimental and commercial artificial saliva formulations on the activity and viability of microcosm biofilm and on enamel demineralization prevention in head and neck cancer (HNC) patients: in vitro studies - Silva, Natara Dias Gomes da (2024)
This thesis reports two manuscripts with the aim of evaluating the antibacterial and anticaries effects of different experimental formulations of artificial saliva containing CaneCPI-5 and/or hemoglobin as well as the commercial salivary substitute BioXtra, using a microcosm biofilm model on enamel, through the acquired enamel pellicle (AEP) engineering concept. The first study assessed the antibacterial and anticaries effects of experimental formulations of artificial saliva containing CaneCPI-5, hemoglobin, or a combination of both proteins, as well as the commercial salivary substitute BioXtra, on the microcosm biofilm formed on irradiated bovine enamel from the saliva of head and neck cancer (HNC) patients undergoing radiotherapy. The second study evaluated the antibacterial, anti-biofilm, and anticaries effects of BioXtra on the microcosm biofilm formed on non-irradiated and irradiated bovine enamel, using saliva from healthy volunteers (control group) or irradiated HNC patients (HNC group). The microcosm biofilm was produced on irradiated (70 Gy) or non-irradiated bovine enamel from human saliva (irradiated HNC patients with hyposalivation or healthy participants with normal salivary flow) mixed with McBain saliva, under exposure to 0.2% sucrose, and submitted to treatments daily (1 min) for 5 days. Bacterial metabolic activity (resazurin), biofilm viability (colony-forming units count CFU, and confocal microscopy), and enamel demineralization (transverse microradiography, TMR) were determined. Data were statistically compared using ANOVA/Tukey and Kruskal- Wallis/Dunn (p < 0.05). In the first study, no significant effects were observed for the different experimental treatments for any of the evaluated parameters. BioXtra® (BXT) significantly reduced the counts of lactobacilli, demonstrating antibacterial potential only for this group. Chlorhexidine (CHX) was an effective treatment, significantly reducing all parameters, serving as an important antimicrobial and anticaries agent. In the second study, BXT significantly reduced the bacterial metabolic activity for both enamel types and both inoculum sources, being more effective for irradiated enamel and saliva from the control group. Similarly, BXT significantly reduced biofilm viability, CFU for total microorganisms, mutans streptococci, and lactobacilli, and was able to significantly reduce mineral loss and lesion depth compared to the negative control. CHX treatment was effective in significantly reducing all parameters, performing better than BXT and reinforcing its efficiency as a reliable positive control. Therefore, BioXtra® exhibited antibacterial, anti-biofilm, and anti-caries effects in this model, and its use is recommended as a commercial positive control for evaluating experimental artificial salivas for HNC undergoing radiotherapy patients. Due to the lack of efficacy, future in vitro studies should be conducted using a new approach to design experimental formulations.